MANAGEMENT OF THE INTERNATIONAL DISTRIBUTION CHANNELS IN THE SMEs INTERNATIONAL BUSINESS STRATEGY - Vapa Tankosić, Jelena; Vapa, Bojan (International Journal of Economic Practice and Policy, 2020)
Companies implementing a strategy based on entering foreign markets have to make a decision on choosing an adequate international distribution channels. Well implemented international distribution system in export-oriented companies can help them improve their competitiveness and better position their products in foreign markets. It is for this reason that the subject of this research paper is to analyze the factors of international distribution from the aspect of international business strategy of SMEs. The research conducted covered various factors related to international distribution strategies such as the ability to deliver international goods quickly and continuously, the established adequate international distribution network, the ability to respond quickly to international partners orders and the effective management of international distributors or agents. The survey was conducted in 50 companies that export various types of products on the territory of the Republic of Serbia. The results of the regression analysis indicate that an adequate distribution network has an impact on sales volume and foreign market share, so that we can conclude that the proper selection of an appropriate distribution network can contribute to enhancing the export potential of the company